Teaching Medical Advances in a Time of Crisis: A Human Microbiome Data Interpretation E-Learning Elective for Medical Students - Cervantes, Jorge L (International Journal of Educational Studies, 2021)
Medical schools were upended by the COVID-19 pandemic resulting in suspension of all in-person educational activities, and leaving clinical clerkships on hold. Emerging medical advances need to be integrated in undergraduate medical curriculum as evidence continues to evolve regarding their clinical application. Here, we describe an innovative distance- learning elective course developed to keep fourth year medical students abreast of important scientific advances. Within each module, each successive entry introduced concepts with increasing complexity and included up-to-date literature material to help in the learning progression. Students’ overall satisfaction was high, as the elective helped them gain personal confidence, improved their medical and intellectual skills, increased their curiosity in medical science, and allowed them to analyze scientific literature they did not understand before.